Red ginseng dietary fiber promotes probiotic properties of Lactiplantibacillus plantarum and alters bacterial metabolism - Jeon, Hyeon Ji; You, Seung-Hwan; Nam, Eoun Ho; Truong, Van-Long; Bang, Ji-Hong; Bae, Yeon-Ji; Rarison, Razanamanana H. G.; Kim, Sang-Kyu; Jeong, Woo-Sik; Jung, Young Hoon; Shin, Minhye (Frontiers in Microbiology, 2023)
Korean red ginseng has been widely used as an herbal medicine. Red ginseng dietary fiber (RGDF) is a residue of the processed ginseng product but still contain bioactive constituents that can be applied as prebiotics. In this study, we evaluated changes on fermentation profiles and probiotic properties of strains that belong to family Lactobacillaceae with RGDF supplementation. Metabolomic analyses were performed to understand specific mechanisms on the metabolic alteration by RGDF and to discover novel bioactive compounds secreted by the RGDF-supplemented probiotic strain. RGDF supplementation promoted SCFA production, carbon source utilization, and gut epithelial adhesion of L. plantarum and inhibited attachment of enteropathogens. Intracellular and extracellular metabolome analyses revealed that RGDF induced metabolic alteration, especially associated with central carbon metabolism, and produced RGDF-specific metabolites secreted by L. plantarum, respectively. Specifically, L. plantarum showed decreases in intracellular metabolites of oleic acid, nicotinic acid, uracil, and glyceric acid, while extracellular secretion of several metabolites including oleic acid, 2-hydroxybutanoic acid, hexanol, and butyl acetate increased. RGDF supplementation had distinct effects on L. plantarum metabolism compared with fructooligosaccharide supplementation These findings present potential applications of RGDF as prebiotics and bioactive compounds produced by RGDF-supplemented L. plantarum as novel postbiotic metabolites for human disease prevention and treatment.